K-RAS4A: Lead or Supporting Role in Cancer Biology? - Aran, Veronica (Frontiers in Molecular Biosciences, 2021)
The RAS oncogene is one of the most frequently mutated genes in human cancer, with K-RAS having a leading role in tumorigenesis. K-RAS undergoes alternative splicing, and as a result its transcript generates two gene products K-RAS4A and K-RAS4B, which are affected by the same oncogenic mutations, are highly homologous, and are expressed in a variety of human tissues at different levels. In addition, both isoforms localise to the plasma membrane by distinct targeting motifs. While some evidence suggests nonredundant functions for both splice variants, most work to date has focused on K-RAS4B, or even just K-RAS (i.e., without differentiating between the splice variants). This review aims to address the most relevant evidence published regarding K-RAS4A and to discuss if this “minor” isoform could also play a leading role in cancer, concluding that a significant body of evidence supports a leading role rather than a secondary role for K-RAS4A in cancer biology.